2008
DOI: 10.1007/s00464-008-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic sphincterotomy versus needle knife precut in difficult biliary cannulation

Abstract: In difficult cannulation, a pancreatic sphincterotomy to achieve deep biliary duct cannulation can be performed with a high success rate (failure rate less than 3%). The corresponding success rate using the needle knife precut technique is 71%. In both methods the risk for post-ERCP pancreatitis is comparable to that of a standard biliary sphincterotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 22 publications
2
78
5
Order By: Relevance
“…In one study, two or more pancreatic duct injections with contrast material were shown to be a significant risk factor for post-ERCP pancreatitis [21] . On the other hand, in the Halttunen et al [22] study, the number of contrast injections was not confirmed to be a risk factor for post-ERCP pancreatitis.…”
Section: Complications and Risk Of Difficult Cannulation In Ercpmentioning
confidence: 79%
See 2 more Smart Citations
“…In one study, two or more pancreatic duct injections with contrast material were shown to be a significant risk factor for post-ERCP pancreatitis [21] . On the other hand, in the Halttunen et al [22] study, the number of contrast injections was not confirmed to be a risk factor for post-ERCP pancreatitis.…”
Section: Complications and Risk Of Difficult Cannulation In Ercpmentioning
confidence: 79%
“…Of course, if endoscopic methods fail, the transhepatic route can be used directly without an endoscopist or the rendezvous technique can be applied, depending on the problem. [3,30] Standard catheter with guide wire 81 [3] Sphincterotome 78 to 84 [4,29] Sphincterotome with guide wire 97 to 99 [26,30] Success in difficult cannulation after primary failure with standard method Persistence 73 to 75 [2,49] Needle knife 67 to 91 [2,6,9,34,37] Erlangen knife 78 to 100 [32,50] Pancreatic sphincterotomy 91 to 100 [10,12,13,22,40,41] Pancreatic stent 97 to 100 [28,47] Pancreatic guide wire 73 to 93 [5,8] Pancreatitis rate after difficult cannulation Persistence 2-4 [2,49] Needle knife 1-11 [2,6,9,34,37] Erlangen knife 3-7 [32,50] Pancreatic sphincterotomy 0-12 [10,12,13,22,40,41] Pancreatic stent 5-7 [28,47] Pancreatic guide wire 0-2 [5,8] Randomized controlled tri...…”
Section: Solutions For Overcoming Difficult Cannulationmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Zang et al 56 reported that both guidewire assisted TPP and needle-knife sphincterotomy (NKS) were associated with relatively low PEP (7%) in otherwise low-risk patients. Halttunen et al 23 reported a low risk of PEP after TPP overall (9%) but the risk was excessive (25%) in patients with PSC. Pancreatic stenting is recommended after attempted TPP when performed over a guidewire.…”
Section: Procedures Factorsmentioning
confidence: 99%
“…Not surprisingly, prior PEP is also considered a risk factor for PEP. 12,13,20,22 Patients with primary sclerosing cholangitis (PSC) are at higher risk for PEP 23 ; this is perhaps due to sclerosis of the papilla leading difficult cannulation and/or impaired pancreatic drainage.…”
Section: Patient Factorsmentioning
confidence: 99%